2021
DOI: 10.31629/kemudi.v6i01.3660
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Komunitas Adat Terpencil (KAT) Oleh Pemerintah Daerah Kabupaten Bengkalis

Abstract: In general, the problem associated with Remote Indigenous Communities is accessibility to public facilities that enable them to transform their lives into a better direction. Lack of accessibility to the outside world which causes Remote Indigenous people to fall into various aspects of life such as poverty, low health levels, education levels and others. The purpose of this study was to analyze the Remote Indigenous Community Empowerment by the Bengkalis Regency Government. The results of this study are usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…They are 1) geographical conditions that make it very difficult for indigenous people to reach access to education; 2) inadequate means and supplies; 3) the variety of indigenous people's cultures that are mostly still preserved, both their respective cultures and traditions; 4) characteristics and lifestyles that indigenous people have that are so difficult to be included in formal education generally. In their study, Andriyus et al (2021) found that the regional government's empowerment of remote indigenous communities, particularly in the Bengkalis district, has not been fully optimized. The efforts made by the government remained limited to assisting in providing educational facilities and opportunities for formal education.…”
Section: Resultsmentioning
confidence: 99%
“…They are 1) geographical conditions that make it very difficult for indigenous people to reach access to education; 2) inadequate means and supplies; 3) the variety of indigenous people's cultures that are mostly still preserved, both their respective cultures and traditions; 4) characteristics and lifestyles that indigenous people have that are so difficult to be included in formal education generally. In their study, Andriyus et al (2021) found that the regional government's empowerment of remote indigenous communities, particularly in the Bengkalis district, has not been fully optimized. The efforts made by the government remained limited to assisting in providing educational facilities and opportunities for formal education.…”
Section: Resultsmentioning
confidence: 99%
“…Proses ini terdiri dari tiga nilai: kelestarian hidup, harga diri, dan kebebasan. Partisipasi masyarakat dalam proses pembangunan, mulai dari perencanaan dan pengambilan keputusan hingga pelaksanaan, merupakan salah satu bentuk aktualisasi pemberdayaan masyarakat (Andriyus et al, 2021).…”
Section: Pemberdayaanunclassified